Corrosion Behavior of Ti-6Al-4V Alloy in Different Media - Abdulmageed, Majid H.; Ibrahim, Slafa I. (Al-Khwarizmi Engineering Journal, 2010)
In this work the corrosion behavior of Ti-6Al-4V alloy was studied by using galvanostatic measurements at room temperature in different media which includ sodium chloride (food salt), sodium tartrate (presence in jellies, margarine, and sausage casings,etc.), sodium oxalate (presence in fruits, vegetables,etc.), acetic acid (presence in vinegar), phosphoric acid (presence in drink), sodium carbonate (presence in 7up drink,etc.), and sodium hydroxide in order to compare. Corrosion parameters were interpreted in these media which involve corrosion potential( Ecorr) and corrosion current density (icorr), since the results of (Ecorr) indicate that Oxalate ions are more corrosive than other materials while the results of (icorr) indicate that NaCl is more corrosive than other materials. Cathodic and Anodic Tafel slopes that were used to calculate the polarization resistance (Rp) to know which materials effect on Ti-6Al-4V alloy uses in dental materials and the results of (Rp) were: Na2CO3 >Oxalate >H3PO4 >CH3COOH >NaOH >Tartrate >NaCl. The change in free energy (∆G) and rate of corrosion in (mpy) were calculated, and the results of rate indicate that increasing in the following sequences: NaCl>Tartrate >NaOH >Oxalate> CH3COOH> H3PO4> Na2CO3.